Konsep Robbani dalam Pendidikan Islam - Noorhayati, Siti Mahmudah (Al-Riwayah : Jurnal Kependidikan, 2019)
This study aims to discuss how the concept of rububiyyah in the perspective of the Koran. The discussion departed from the background of the concept that the scholars had conveyed various views. This study refers to the opinion expressed by Quraish Shihab which is the essence of the opinion of the scholars that the root word "Allah" is Aliha Ya'lahu which is calm, because when with Him the heart becomes calm. Or in another sense that is "menunju" and "begging for", since all beings rely on Him and to Him all beings beg for. The stage of concept formulation is taken from the series of revelation by revelation. Then chronologically, the conception of the rububiyyah was formed with the confirmation of the revelations thereafter. The discussion here has significance in terms of formulation of limits, implementation, the concept of rububiyyah accurately in accordance with the verses of the Qur’an. Overall, the written concept of rububiyyah is not written literally in the Qur'an, but its meaning is implied in the verses revealed gradually. By its nature, the concept of rububiyyah includes the notion that God is the one who possesses and controls of everything. And finally, the concept of rububiyyah is as the Preserver of the universe and its manifestations are human attitudes in maintaining and managing the universe well, attitudes to increase spiritual values, and attitudes of determination for the happiness of life in the world and the hereafter